Tingkat Partisipasi Kerja dan Karakteristik Sosial Ekonomi Pedagang Perempuan di Kecamatan Bangli Kabupaten Bangli (Studi Kasus di Pasar Kidul) - Dewi, I Gusti Ayu Made Oktavia Utami; Tisnawati, Ni Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 7, Juli 2017 (pp. 1157 - 1394), 2017)
This study aimed to analyze the socio-economic influence on the level of labor participation of women workers in District Bangli with a case study in the Kidul Market. This research was conducted in Kidul Market District Bangli, with a sample of 92 respondents out of a total population of 1075. The samples with Stratified Random Sampling method. Methods of data analysis used in this research is multiple linear regression model with a participation rate of working women workers as the dependent variable and the five independent variables are income, income of husband, age, education level, number of dependents, and spending household. Mechanical execution of research using interviews with questionnaires and observation. From the research results that positive and significant of revenue, significant negative effect of revenue husband, positive and significant effect of age, significant negative effect of educational level, positive and significant effect of the number of family, and significant positive effect of household spending.
Keywords: Tingkat Partisipasi Kerja; Pedagang Perempuan; Pendapatan; Umur; Tingkat Pendidikan; Jumlah Tanggungan Keluarga; Pengeluaran Rumah Tangga